The impact of attending day care designed for home-dwelling people with dementia on nursing home admission: a 24-month controlled study - Anne Marie Mork Rokstad; Knut Engedal; Øyvind Kirkevold; Jūratė Šaltytė Benth; Geir Selbæk (BMC Health Services Research, 2018)
Abstract Background Day care services offer meaningful activities, a safe environment for attendees and respite for family caregivers while being expected to delay the need for nursing home (NH) admission. However, previous research has shown inconsistent results regarding postponement of NH admission. The objective of the study was to explore the influence of a day care programme designed for home-dwelling people with dementia on NH admission. Method A quasi-experimental trial explored the proportion of patients permanently admitted to nursing homes after 24 months as the main outcome by comparing a group of day care attendees (DG) and a group of participants without day care (CG). In all, 257 participants were included (181 in DG and 76 in CG). A logistic regression model was developed with NH admission as the outcome. Participant group (DG or CG) was the main predictor, baseline patient and family caregiver characteristics and interactions were used as covariates. Results The mean age of participants was 81.5 (SD 6.4), 65% were women and 53% lived alone. The mean MMSE score was 20.4 (SD 3.5). In all, 128 (50%) of the participants were admitted to a nursing home by the 24-month follow-up, 63 participants (25%) completed the follow-up assessment and 66 (26%) dropped out due to death (8%) and other reasons (18%). In the logistic unadjusted regression model for NH admission after 24 months, participant group (DG or CG) was not found to be a significant predictor of NH admission. The results from the adjusted model revealed that the participant group was associated with NH admission through the interactions with age, living conditions, affective symptoms, sleep symptoms and practical functioning, showing a higher probability for NH admission in DG compared to CG. Conclusion The study reveals no evidence to confirm that day care services designed for people with dementia postpone the need for NH admission. Admission to nursing homes seems to be based on a complex mix of personal and functional characteristics both in the person with dementia and the family caregivers. The findings should be considered in accordance with the limitation of inadequate power and the high drop-out rate. Trial registration The study is registered in Clinical Trials (NCT01943071).